Serum Lactate Dehydrogenase Levels with Birth Asphyxia in Term Neonates - Parveen Kumar Antil (Journal of Clinical and Diagnostic Research, 2020)
Introduction: It is difficult to diagnose birth asphyxia if neonatal records are not available. Serum Lactate Dehydrogenase (LDH) level is an easily accessible tool in most of routine laboratories. Aim: To assess the relation of serum LDH with birth asphyxia in term neonates. Materials and Methods: This was a prospective study, done on 50 asphyxiated newborns (cases) and 50 non asphyxiated term newborns (controls) which were taken from Neonatal Intensive Care Unit (NICU), Department of Paediatrics, Maharishi Markandeshwar Institute of Medical Sciences and Research, Ambala, Haryana, India from November 2017 to September 2019. LDH levels were estimated in 50 non asphyxiated neonates of Cord Blood (CB) at birth and in 50 asphyxiated newborns of CB at birth and at 24 hours of life. Chi-square test, Fischer-exact test and student’s t-test were applied in this study. The Software used to analyse and compute data was SPSS version 20. Results: On comparing the controls and cases, mean LDH of CB was 299.90 U/L vs. 999.04 U/L. Mean LDH level in cases at 24 hours was 1574.72 U/L. LDH (CB) sensitivity was 94% with Confidence Interval (CI) 83.45% to 98.75%, specificity was 90.00% with CI 78.19% to 96.67%. The Positive Predictive Value (PPV) and Negative Predictive Value (NPV) of LDH were estimated as 90.38%, 93.75%, respectively. The LDH (CB) value in mild, moderate and severe asphyxia was 585.33±424.78 U/L, 694.91±444.22 U/L, 1369±672.59 U/L, respectively. The LDH at 24 hours of postnatal life values in mild, moderate, severe asphyxiated newborns were 772.33±108.61 U/L, 1103.69±605.25 U/L, 2457±1019.81 U/L, respectively and it showed a highly significant p-value of <0.001. LDH level at 24 hours had more area under curve so have more diagnostic value than LDH (CB) (0.861 vs 0.725), both timing is good for differentiating asphyxiated and normal neonates. Conclusion: The present study found a good correlation between LDH levels in cases with severity of birth asphyxia. It concluded that LDH at 24 hours is a more accurate time to differentiate newborn with birth asphyxia than without birth asphyxia. The LDH for diagnosis of birth asphyxia can be used in cases without past records or sick newborns which are referred from peripheral hospitals.